2011
DOI: 10.1177/1534650110395013
|View full text |Cite
|
Sign up to set email alerts
|

Functional Assessment and Behavioral Treatment of Skin Picking in a Teenage Girl With Prader-Willi Syndrome

Abstract: Skin picking is common in individuals with Prader-Willi Syndrome (PWS) but few treatment studies exist. This study reports the successful functional behavioral assessment (FBA) and treatment of skin picking in a 16-year-old female with PWS. A treatment package based on FBA results consisted of differential reinforcement for alternative and incompatible behavior, selfevaluation of progress, and reinforcement for weekly progress and participation in treatment. Pictures of wounds resulting from skin picking were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
1
6
0
4
Order By: Relevance
“…In Prader–Willi syndrome, two case studies have been published of interventions for reducing the occurrence of skin‐picking a common problematic behaviour in the syndrome. Radstaake et al . (2011) reported on the successful use of functional behavioural assessment and treatment of skin picking in a 16‐year‐old female with the syndrome.…”
Section: Cognitive and Behavioural Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Prader–Willi syndrome, two case studies have been published of interventions for reducing the occurrence of skin‐picking a common problematic behaviour in the syndrome. Radstaake et al . (2011) reported on the successful use of functional behavioural assessment and treatment of skin picking in a 16‐year‐old female with the syndrome.…”
Section: Cognitive and Behavioural Interventionsmentioning
confidence: 99%
“…In Prader-Willi syndrome, two case studies have been published of interventions for reducing the occurrence of skin-picking a common problematic behaviour in the syndrome. Radstaake et al (2011) reported on the successful use of functional behavioural assessment and treatment of skin picking in a 16-year-old female with the syndrome. Stokes & Luiselli (2009) describe a study where the skin picking of a 26-year-old male with Prader-Willi was reduced by restricting the individual's access to the setting in which skin picking most often occurred (i.e.…”
Section: Intervention Studiesmentioning
confidence: 99%
“…Las características fenotípicas intervenidas fueron lenguaje (Bellon-Harn, 2005; Misquiatti, Cristovão y Brito, 2011), habilidades adaptativas (Dolyniuk et al, 2002; Gardner y Wolfe, 2015), hiperfagia (Grolla et al, 2011;Messersmith, Slifer, Pulbrook-Vetter y Bellipanni, 2008;Rose y Walker, 2000;Singh et al, 2008;Singh et al, 2011), robo de comida (Maglieri, DeLeon, Rodriguez-Catter y Sevin, 2000), conducta social (Samuels y Stansfield, 2012), pataletas (Messersmith et al, 2008;Rose y Walker, 2000), rascado de piel (Radstaake et al, 2011), rascado rectal (Stokes y Luiselli, 2009) y síntomas obsesivos-compulsivos (Storch et al, 2011).…”
Section: Intervencionesunclassified
“…En cuanto a las fases, además de la intervención, seis estudios explicitaron una fase de línea base (Rose y Walker, 2000; Stokes y Luiselli, 2009), un estudio explicitó una fase de seguimiento (Messersmith et al, 2008), cuatro estudios explicitaron tanto fase de línea base como de seguimiento (Gardner y Wolfe, 2015;Samuels y Stansfield, 2012;Singh et al, 2008;Singh et al, 2011) y siete estudios no explicitaron ninguna de las dos (Bellon-Harn, 2005;Dolyniuk et al, 2002;Grolla et al, 2011;Maglieri et al, 2000;Misquiatti et al, 2011;Radstaake et al, 2011;Storch et al, 2011).…”
Section: Intervencionesunclassified
See 1 more Smart Citation